Sustainability in undergraduate course curricula at Andalusian (Spain) universities: a critical analysis - Aranda, Lourdes; Rumiche Chávarry, Rocío del Pilar; Ríos-Ariza, José Manuel; Mena-Rodríguez, Esther (Frontiers in Education, 2024)
Education is one of the main tools used to implement sustainable development goals (SDGs). Higher education institutions (HEIs) have a major social responsibility regarding sustainability given the relevance and impact of their educational work and the creation of knowledge through their research. Sustainability is promoted and linked to values, teaching-learning methodologies, and studing of global-local problems. Within this framework, the objective of our research is to determine the presence and means by which sustainability appears in the course curricula of university bachelor's degrees of the public universities of Andalusia (Spain). The study used quantitative methodology. As in other studies, major deficiencies have been revealed in terms of the inclusion of sustainability in the universities, determining a limited presence of local problems to address sustainability. Thus, Andalusian universities distance themselves from the society and community in which they exist. This may also limit student knowledge of sustainability issues in which they could potentially be relevant participants.